F-18 Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography in the Staging of Linitis Plastica Caused by Primary Gastric Adenocarcinoma - Santhosh Sampath (World Journal of Nuclear Medicine, 2013)
Diffuse infiltration by a primary or metastatic malignancy into the submucosa and muscularis of the stomach (linitis plastica [LP]) has been described in literature. The authors present a case of LP caused by primary adenocarcinoma of the stomach, showing diffuse Fluorine-18 fluorodeoxyglucose uptake in the thickened wall of the stomach.